Impact of colchicine on inflammatory markers and pregnancy outcomes in familial Mediterranean fever patients - Tokgöz Çakır, Betül; Aktemur, Gizem; Karabay, Gülşan; Şeyhanlı, Zeynep; Vanlı Tonyalı, Nazan; Akın, Furkan; Afsar, Salime Nur; Çelen, Şevki (The European Research Journal, 2025)
Objectives: The aim of this study is to evaluate the effect of colchicine use on maternal inflammatory markers and pregnancy outcomes in pregnant women diagnosed with Familial Mediterranean Fever (FMF) and receiving colchicine therapy. Methods: This retrospective analysis included 42 pregnant women diagnosed with FMF who underwent colchicine treatment and 126 healthy pregnant controls. Neutrophil/Lymphocyte Ratio (NLR), Platelet/Lymphocyte Ratio (PLR), and Monocyte/Lymphocyte Ratio (MLR) rates in the blood of the groups in the first trimester, obstetric morbidities and pregnancy outcomes were compared. Results: The patient cohort had markedly reduced hemoglobin levels (12.15±1.36 vs. 12.80±1.02 g/dL, P=0.001), an elevated prevalence of anemia (19% vs. 3%, P=0.002), and diminished monocyte counts (0.55 vs. 0.61 ×10⁹/L, P=0.022) as well as decreased MLR values (0.27 vs. 0.29, P=0.020) in comparison to the control group. Other inflammatory markers, pregnancy complications, and neonatal outcomes were similar between the groups (p>0.05). Conclusions: Colchicine seems to be useful in managing inflammation during FMF pregnancies without negatively affecting pregnancy or neonatal outcomes. Thorough prenatal care, encompassing anemia monitoring, is crucial for enhancing mother and fetal health.